The Effect of Occupational Safety and Health (K3) on Employee Performance at PT. Kawanua Dasa Pratama Paniki Manado Branch (Productivity, 2024)
The purpose of this research is to determine the influence of occupational safety and health on employee performance at PT. Kawanua Dasa Pratama (Manado Paniki Branch). This research uses quantitative research. The population and sample used were Company Managers and Employees at PT. Kawanua Dasa Pratama (Manado Paniki Branch). Data collection techniques in this research were questionnaires, observation, literature study and documentation. The sample used in this research was 57 employee respondents. Data collection was carried out by administering a questionnaire. The data analysis technique used in this research uses SPPS Version 25. The results of this research show that occupational safety and health have an influence on employee performance. Hypothesis test results show that occupational safety and health influence employee performance at PT. Kawanua Dasa Pratama (Paniki Manado Branch).